The Right to a Fair Trial of Legal Persons Throughout the Case Law of the ECHR and the CJEU - Sokolova, Mariia (LeXonomica, 2023)
The ambition of this article is an analysis of the right to a fair trial of legal entities through the prism of the jurisprudence of the ECtHR and the CJEU. Despite the factual admission of the right to a fair trial to companies in the case law of the Courts, the absence of a strong theoretical foundation and persuasive explanation in their judgments raises ambiguity as to the ECtHR and the CJEU positions in that regard. In that context, the article examines landmark cases of both Courts and relevant doctrinal considerations concerning the application of guarantees provided by the right to a fair trial to legal persons. The ECtHR case law is considered inconsistent and the Strasbourg court, it appears, tries to avoid any far-reaching conclusions. The CJEU in its case law, due to the inherent focus of EU law on economic values, interprets the right to a fair trial of companies broadly, and sometimes, broader than it is needed. It is concluded that the issue requires more attention from both the Courts and legal scholars, in the view of serious consequences the ignorance and unfounded admission of any fundamental right could entail to the society and economy.PovzetekNamen tega članka je analiza pravice pravnih oseb do poštenega sojenja skozi prizmo sodne prakse ESČP in Sodišča EU. Kljub dejanskemu priznavanju pravice do poštenega sojenja gospodarskim družbam v sodni praksi sodišč odsotnost trdne teoretične podlage in prepričljive razlage v njihovih sodbah povzroča nejasnosti glede stališč ESČP in SEU v zvezi s tem. V tem kontekstu so v članku obravnavane prelomne zadeve obeh sodišč in ustrezni doktrinarni premisleki glede uporabe jamstev, ki jih zagotavlja pravica do poštenega sojenja, za pravne osebe. Sodna praksa ESČP velja za nedosledno, sodišče v Strasbourgu pa se, kot kaže, poskuša izogniti daljnosežnim sklepom. Sodišče EU v svoji sodni praksi zaradi inherentne osredotočenosti prava EU na gospodarske vrednote pravico do poštenega sojenja družb razlaga široko in včasih širše, kot je to potrebno. Ugotavlja se, da je treba temu vprašanju nameniti več pozornosti tako s strani sodišč kot pravnih strokovnjakov, in sicer zaradi resnih posledic, ki bi jih nepoznavanje in neutemeljeno priznavanje katere koli temeljne pravice lahko imelo za družbo in gospodarstvo.